Defining Cystoid Macular Degeneration in Diabetic Macular Edema: An OCT-Based Single-center Study - Gökçen Yalçın; Şengül Özdek; Fatma Nur Baran Aksakal (Türk Oftalmoloji Dergisi, 2019)

(untitled)
Objectives:To describe cystoid macular degeneration (CMD), which has no clear definition in diabetic macular edema (DME), and examine its features in optical coherence tomography (OCT) and fundus fluorescein angiography (FFA).Materials and Methods:This study was conducted using OCT images of patients who were followed in Gazi University between November 2011 and March 2015. A total of 259 eyes (187 patients) found to have cystic changes on OCT were included. Macular ischemia, peripheral ischemia, and type of edema were identified on FFA. Vitreomacular interface abnormalities, foveal contour integrity, internal reflectivity of the cysts, and outer retinal layer defects were analyzed from OCT images. The horizontal and vertical diameters of the largest cyst within 1000 μm of the foveal center were measured for the definition of CMD. Cut-offs for these values were determined by receiver operating characteristic curve analysis. Cystoid macular edema (CME) and CMD groups were created and their characteristics were analyzed.Results:The horizontal and vertical diameters of the largest cyst were moderately positively correlated with visual acuity (rs=0.349, r=0.419, respectively). Eyes with horizontal diameter of the largest cyst ≥450 μm were classified as CMD; in this group, sensitivity in the prediction of visual acuity ≤20/60 was 58%. Eyes with horizontal diameter of the largest cyst <450 μm were classified as CME; in this group, specificity in the prediction of visual acuity >20/60 was 73%. For the threshold of 300 μm determined for vertical diameter of the largest cyst, sensitivity was 62% and specificity was 69%. The CME and CMD groups were formed according to these cut-off values. Compared to the CME group, the CMD group had greater central subfield thickness and higher prevalence of outer retinal damage, severe disruption of foveal contour, macular ischemia, and diffuse/mixed type edema.Conclusion:In eyes with DME, CMD can be defined as the largest cyst within 1000 μm of the foveal center having a horizontal diameter of ≥450 μm and vertical diameter ≥300 μm, especially if associated with macular ischemia, outer retinal damage, loss of foveal contour, and diffuse/mixed type edema.